Budgeting : a comparative theory of budgetary processes - Wildavsky, Aaron B. (Boston : Little, Brown, 1975)
The purpose of this book is to collect in one place existing knowledge on budgeting. By "existing" I mean reasonably reliable accounts of how budgeting is carried on in a particular level of government.
Includes index.
Includes bibliographical references: p. 405-424.
hza 27/08/2018
Loans
Keywords: Budget; Program budgeting